Productive performance and quality of blueberry fruits subjected to rejuvenation pruning - I. R. Holz; L. O. Fischer; A. R. Bergmann; F. G. Herter; M. S. Pasa; P. C. Mello-Farias (Brazilian Journal of Biology)
Abstract The objective of this research was to evaluate the effect of rejuvenating pruning of blueberry cultivars Bluegem and Powderblue in relation to fruit production and quality parameters. The experiment was carried out in a commercial orchard established in 2004 in the Municipality of Morro Redondo/RS, Brazil. The bushes were spaced 3.0x1.0 m apart. The treatments consisted of: no pruning, conventional pruning (homemade), moderate pruning (suppression of 50% of canes with a diameter greater than 50mm) and drastic pruning (suppression of 100% of canes with a diameter greater than 50mm). The experimental design was in randomized blocks, in a 2x4 factorial arrangement, with two cultivars and four pruning managements, with four replications. The production parameters and physical-chemical quality were evaluated in two production cycles and the characterization of shoots was carried out in the last cycle. It was observed that the absence of pruning in Bluegem reduces the quantity of buds per shoot. Furthermore, there was no difference in production in the second year of evaluation. Drastic pruning also increases the weight and size of the fruits of the Bluegem and Powderblue cultivars in the first year.